Translation and validity of the Scale of beliefs about the use of masks to prevent the spread of COVID-19 - Henry Santa-Cruz-Espinoza; Natalia Mavila Guzmán Rodríguez; Patricia Ibeth Tirado Bocanegra; Jessica Esther Mendo Zelada; Geraldine Vanessa Morales Domínguez (Revista Cubana de Medicina Militar)
Introduction: The use of a mask is essential to reduce the spread of COVID-19, however, a significant percentage of people refuse to use it. Beliefs may play an important role in accepting or rejecting their use. Objective: To translate and determine the evidence of validity of internal structure and reliability of the self-report of beliefs about the use of masks. Methods: The self-report of beliefs about the use of masks was administered to 1218 people from different provinces of Peru (Mage = 27,4 years, SD = 12,6), chosen in a non-probabilistic way. The instrument was subjected to a process of double translation from English to Spanish and vice versa; In addition, using the Jamovi Project version 1.6 program, the internal structure was determined with factor analysis (exploratory and confirmatory), and finally reliability was estimated. Results: The exploratory factor analysis identified four emerging factors that explained 53.7% of the variance. The model was verified and obtained acceptable fit indices (χ² = 154 gl = 46; p < 0,01; CFI = 0,96; TLI = 0,942; RMSEA = 0,602). In addition, standardized factor loadings greater than 0,30 were observed. Conclusions: The Spanish version of the self-report of beliefs about the use of masks shows evidence of validity of structure and reliability due to adequate internal consistency.